REFORESTASI BANGKA POA OLEH ANAK WASO COMMUNITY (AWAS.COM) DI WILAYAH ADAT GENDANG WASO, MANGGARAI (Sebuah Riset Sosial) - Marianus Tapung; Max Regus; Inosensius Sutam; Marsel R. Payong; Marianus S. Jelahut (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
The effort to maintain the balance of the natural environment is the responsibility of all humans on earth. The Waso Community (Anak Waso Community, AWAS.com) and the Waso indigenous community have been trying to carry out their responsibilities by carrying out reforestation activities for three years. To see the extent of these efforts carried out and get its impact, it is necessary to do social research. The main objective of this social research is to observe and evaluate comprehensively the steps of the Waso children's community in carrying out reforestation activities for three years in the Bangka Poa region, as well as the impact of the activities carried out. To describe the efforts of the Awas.Com community in protecting the environment, researchers conducted social research carried out using the Planning, Organizing, Acting, Impact (POAI) method. The research results illustrate that this reforestation activity has shown a positive impact in the form of the recovery of the natural conditions of the Bangka Poa region and the stable water debit in several springs. The research study also looks at and evaluates that reforestation activities for three years in a row have had a direct or indirect impact on the growth and development of ecological, sociological, economic and religious awareness and responsibilities in the community and Waso young generation.